SDRE-Based Integral Sliding Mode Control for Wind Energy Conversion Systems - Bayandy Sarsembayev; Kanat Suleimenov; Botagoz Mirzagalikova; Ton Duc Do (IEEE, 2020)
This paper proposes a novel integral sliding mode control (ISMC) scheme for wind energy conversion systems (WECSs) equipped with permanent magnet synchronous generators (PMSGs), based on numerically solving a state‑dependent Riccati equation (SDRE). The control design incorporates nonlinear near‑optimal feedback via Taylor series approximations of SDRE solutions, continuous algebraic Riccati and Lyapunov equations, and sliding variables that eliminate the reaching phase. A high‑order disturbance observer further enhances stability. Compared to linear methods like LQR and conventional ISMC, the proposed method achieves superior performance under model uncertainties, though increasing Taylor terms improves accuracy at the cost of computational load. Simulations in MATLAB/Simulink confirm its effectiveness under nominal and uncertain conditions.,
Keywords: wind energy; fault-tolerant control; SDRE; sliding mode